2016
DOI: 10.5057/ijae.ijae-d-16-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Both Similarity of the Evaluation of Impressions, Between Elements, and Font Legibility, on Aesthetic Impression of Packaging

Abstract: A previous study has shown that there is a statistical similarity between the evaluation of impressions of Japanese fonts and of tea beverage package design. Recent research indicates that readable font design is related to subjective fluency. Here, we tested the effects of similarity between the evaluation of impressions of font designs and of package designs, and font legibility, on aesthetic impressions of packaging, using the 16 pictures combining fonts and packaging from the previous study. Thirty-four pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This understanding is channeled into communications that are crafted, with varying levels of percept sophistication, to align with consumer preference. Research conducted by Mukai and Miyazaki (2016) revealed a statistical similarity between how consumers perceive Japanese fonts and tea beverage package design, suggesting a possible link between package design and perception of the tea product.…”
Section: Discussionmentioning
confidence: 96%
“…This understanding is channeled into communications that are crafted, with varying levels of percept sophistication, to align with consumer preference. Research conducted by Mukai and Miyazaki (2016) revealed a statistical similarity between how consumers perceive Japanese fonts and tea beverage package design, suggesting a possible link between package design and perception of the tea product.…”
Section: Discussionmentioning
confidence: 96%
“…It is likely that the poor contrast in our non-aesthetic packaging sample led to a low level of visual appeal and to reduced font legibility. As demonstrated in a study focused on tea beverage packages (Mukai and Miyazaki, 2016), font legibility may play a role in rating the overall aesthetic impression of the packaging. Another interesting finding was that positive effect of design principles on attractiveness remained the same even when taking into account whether the beauty of packaging was important for the participants or not.…”
Section: Discussionmentioning
confidence: 99%
“…Desain kemasan harus tepat target dan menyampaikan visual dan isi verbal untuk mengkomunikasikan maksud merek dan informasi produk [3]. Fitur yang perlu diperhatikan dalam desain kemasan untuk semua kalangan yang relevan adalah kemasan harus mudah dibuka dan mudah dibaca informasinya [4].…”
Section: Pendahuluanunclassified
“…Technical response atau respon teknis didapatkan dari studi literatur, wawancara dengan pihak UMKM dan pemasok kemasan, dan telah divalidasi pakar. Respon teknis ini adalah cara pelaku usaha untuk memberikan solusi dan menjawab kebutuhan konsumen [4].…”
Section: Gambar 2 Pemaparan Hasil Desain Kemasan Manisan Rumput Lautunclassified